Characterisation of murine MICL (CLEC12A) and evidence for an endogenous ligand. - Pyz, E; Huysamen, C; Marshall, A; Gordon, S; Taylor, P; Brown, G (2008)
Inhibitory receptors are required for the control of cellular activation and they play essential roles in regulating homeostasis and immunity. We previously identified a human inhibitory C-type lectin-like receptor, MICL (CLEC12A), a heavily glycosylated monomer predominantly expressed on myeloid cells. Here we characterise the murine homolog of MICL (mMICL), and demonstrate that the receptor is structurally and functionally similar to the human orthologue (hMICL), although there are some notable differences. mMICL is expressed as a dimer and is not heavily glycosylated; however, like hMICL, the receptor can recruit inhibitory phosphatases upon activation, and is down-regulated on leukocytes following stimulation with selected TLR agonists. Using novel monoclonal antibodies, we demonstrate that, like the human receptor, mMICL is predominantly expressed by myeloid cells. However, mMICL is also expressed by B cells and CD8+ T cells in peripheral blood, and NK cells in the bone marrow. Finally, we show that mMICL recognises an endogenous ligand in a variety of murine tissues, suggesting that the receptor plays a role in homeostasis.